Impact of Nanoparticle Consolidation on Charge Separation Efficiency in Anatase TiO2 Films - Karin Rettenmaier (Frontiers Media S.A., 2021)
Mesoporous films and electrodes were prepared from aqueous slurries of isolated anatase TiO2 nanoparticles. The resulting layers were annealed in air at temperatures 100°C ≤ T ≤ 450°C upon preservation of internal surface area, crystallite size and particle size. The impact of processing temperature on charge separation efficiency in nanoparticle electrodes was tracked via photocurrent measurements in the presence of methanol as a hole acceptor. Thermal annealing leads to an increase of the saturated photocurrent and thus of the charge separation efficiency at positive potentials. Furthermore, a shift of capacitive peaks in the cyclic voltammograms of the nanoparticle electrodes points to the modification of the energy of deep traps. Population of these traps triggers recombination possibly due to the action of local electrostatic fields attracting photogenerated holes. Consequently, photocurrents saturate at potentials, at which deep traps are mostly depopulated. Charge separation efficiency was furthermore investigated for nanoparticle films and was tracked via the decomposition of hydrogen peroxide. Our observations evidence an increase of charge separation efficiency upon thermal annealing. The effect of particle consolidation, which we associate with minute atomic rearrangements at particle/particle contacts, is attributed to the energetic modification of deep traps and corresponding modifications of charge transport and recombination, respectively.